2018
DOI: 10.1186/s41935-018-0094-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive equations and multiplication factors for stature estimation using foot dimensions of an adult Nigerian population

Abstract: Background: The determination of living stature is a key component of personal identification of individuals. In this study, we developed predictive regression models and multiplication factors to reliably estimate living stature from foot length and breadth in adult Nigerian undergraduate students at the University of Lagos. Materials and methods: The study sample comprised 400 subjects (200 males and 200 females) of Nigerian parentage, aged 18-36 years who volunteered and satisfied the inclusion criteria. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
(87 reference statements)
3
6
0
Order By: Relevance
“…There is positive significant correlation between stature, foot length and width in the studied population. Several studies on the estimation of stature using foot measurements have shown the human feet to be reliable estimate of stature in the forensic identification [6], [7], [9], [11], [23], [25], [26]. The application of predictive regression models has been used by anthropologists to accurately predict stature using anthropometric measurements of body parts such as foot length and breadth [9], [12], [26].…”
Section: Discussionmentioning
confidence: 99%
“…There is positive significant correlation between stature, foot length and width in the studied population. Several studies on the estimation of stature using foot measurements have shown the human feet to be reliable estimate of stature in the forensic identification [6], [7], [9], [11], [23], [25], [26]. The application of predictive regression models has been used by anthropologists to accurately predict stature using anthropometric measurements of body parts such as foot length and breadth [9], [12], [26].…”
Section: Discussionmentioning
confidence: 99%
“…Many earlier studies investigated with regression equation. 8,18,22,23 and multiplication factor 24 for stature determination from foot length. However, a very few study compared these methods for stature determination especially with foot length.…”
Section: Discussionmentioning
confidence: 99%
“…The patterns of sexual dimorphism and bilateral asymmetry in foot morphology and anthropometry in adult Nigerians have been highlighted and elaborated in [1][2][3] also reviewed current metric approaches to predictive regression in their report on the pattern of variation in foot anthropometry and their correlation with stature in young adult Nigerians while [4] attempted to predict sex from foot anthropometry using the discriminant function analysis model in Nigerian adults. However, available data on foot anthropometry in Nigerian sub-adults (children and adolescents) is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…In a review of scholarly research from across the globe, [3] observed that in adults, foot length and breadth measurement predicted stature in a rather robust manner. Foot length performed consistently better than foot breadth in this regard, an observation than was corroborated by previous work by [23]and contemporary work by [24] in Indians.…”
Section: Introductionmentioning
confidence: 99%